(untitled) (Experimental biology, 2016)
Systole pressure is investigational before and after loading for the teenagers of going in for sports. Reduction of indexes of systole pressure is found out for teenagers after loading. On the indexes of research it is necessary anymore to spare attention on the respiratory system and to include more respiratory exercises. These indexes can be used for the estimation of health for the teenagers of different age from force of loading